2016
DOI: 10.1161/atvbaha.116.307848
|View full text |Cite
|
Sign up to set email alerts
|

Role of Axl in T-Lymphocyte Survival in Salt-Dependent Hypertension

Abstract: Objective Survival of immune and non-immune cells relies on Axl, a receptor tyrosine kinase, which is implicated in hypertension. Activated T lymphocytes are involved in regulation of high blood pressure. The goal of the study was to investigate the role of Axl in T lymphocyte functions and its contribution to salt-dependent hypertension. Approach and Results For the first time we report increased apoptosis in peripheral blood from Axl−/− mice due to lower numbers of white blood cells mostly lymphocytes. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 39 publications
2
18
0
2
Order By: Relevance
“…The data indicated that Axl-expressing immune cells drove pro-inflammatory gene expression and increased immune cell infiltration in the kidney at early stages of hypertension and that Axl expression in both immune and vascular cells was detrimental in the later phases of hypertensive disease. Continuing on from this, the same group demonstrated that Axl is critical for survival of T lymphocytes, affecting vascular remodelling and inflammation in DOCA-salt induced hypertension 107 …”
Section: Axl In Cvdmentioning
confidence: 81%
“…The data indicated that Axl-expressing immune cells drove pro-inflammatory gene expression and increased immune cell infiltration in the kidney at early stages of hypertension and that Axl expression in both immune and vascular cells was detrimental in the later phases of hypertensive disease. Continuing on from this, the same group demonstrated that Axl is critical for survival of T lymphocytes, affecting vascular remodelling and inflammation in DOCA-salt induced hypertension 107 …”
Section: Axl In Cvdmentioning
confidence: 81%
“…However, SBP and PP were not significantly different in Axl -/- aging mice compared to WT aging mice with or without testosterone treatment. Korshunov VA [ 35 ] and Batchu N [ 36 ] found Axl deficiency could reduce SBP level in deoxycorticosterone acetate (DOCA)-salt hypertension model, and gas6/Axl contributes to vascular endothelial dysfunction, and remodeling via inhibiting vascular apoptosis, in the late phase of DOCA-salt hypertension. The role of Gas6/Axl on hypertension needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this loss in resistance to the pressor effects of Ang II could be due to a spontaneous mutation(s) that makes the T-cell deficient B6.Rag1 −/− -M no longer a model of Ang II-resistant hypertension. While these findings may call into question the physiological importance of T-cells in Ang II-dependent hypertension, a study by Batchu et al 24 using the same Jackson Laboratory strain of B6.Rag1 −/− -M showed that B6.Rag1 −/− -M were resistant to DOCA-salt-induced hypertension. The SBP increased by only 4 mm Hg in B6.Rag1 −/− -M compared to 21 mm Hg in B6.WT-M or to 19 mm Hg in CD3➔B6.Rag1-M. Taken together, these findings raise the possibility that T-cell modulation of blood pressure may be more dependent on sodium than Ang II in B6.Rag1 −/− -M.…”
Section: Discussionmentioning
confidence: 99%